PENGARUH PUPUK HAYATI MAJEMUK CAIR DAN PUPUK SINTETIK TERHADAP PERTUMBUHAN TANAMAN EDAMAME (Glycine max (L.) Merr) - Fahmi, Lukman; Rahayu, Arifah; Mulyaningsih, Yanyan (JURNAL AGRONIDA, 2017)
Fertilizer administration is a way to increase the productivity of edamame plants.  Synthetic fertilizer is commonly used in edamame cultivation today.  However, excessive use of synthetic fertilizer could reduce soil fertility so that substitution of it with biofertilizer is needed.  This study was aimed at assessing the effects of biofertilizer and synthetic fertilizer administration on the growth and production of edamame plants.  A completely randomized design in a factorial pattern was used.  The first factor was biofertilizer rates consisting of three levels namely no fertilizer (0% R), 5 ml/l (50% R), and 10 ml/l (100% R).  synthetic fertilizer was given in five levels consisting of no fertilizer (0% R), 25% recommended rate (urea 37.5 kg/ha, SP-36 37.5 kg/ha, and KCl 25 kg/ha), 50% recommended rate (urea 75 kg/ha, SP-36 75 kg/ha, and KCl 50 kg/ha), 75% recommended rate (urea 112.5 kg/ha, SP-36 112.5 kg/ha, and KCl 75 kg/ha), and 100% recommended rate (urea 150 kg/ha, SP-36 150 kg/ha, and KCl 100 kg/ha).Results showed that plants given biofertilizer by 100% recommended rate had significantly higher height, number of leaves, and fresh and dry root weight in 5 weeks after planting (WAP).  Synthetic fertilizer administration by 100% recommended rate gave significantly higher plant height, number of branches, number of leaves, and fresh and dry root weight in 5 weeks after planting (WAP).  Interaction of 100% recommended rate of biofertilizer and 100% recommended rate of synthetic fertilizer resulted in significantly higher number of leaves and number of flowers. Keywords: edamame plant. Biofertilizer, synthetic fertilizer